2014 CAV award announcement - Kwiatkowska, M; Vardi, M; Bouajjani, A; Ball, T (Springer, 2016)
The 2014 CAV (Computer-Aided Verification) Award was presented on July 19, 2014, at the 26th annual CAV conference in Vienna to Patrice Godefroid, Doron Peled, Antti Valmari, and Pierre Wolper for the development of partial-order-reduction algorithms for efficient state-space exploration of concurrent systems.